Preferensi Mahasiswa di Kota Pontianak terhadap Makanan Tradisional Kalimantan Barat dan Perbandingan Komposisi Nutrisinya dengan Pangan Siap Saji - Wahdah Wahdah; Lucky Hartanti; Maherawati Maherawati (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2022)
One aspect of cultural diversity is traditional food. Traditional food serves as a means of expressing thanks, performing cultural rituals, building kinship as well as being a source of nutrition. West Kalimantan is one of the multi-ethnic provinces in Indonesia, hence it offers a wide range of traditional foods. The existence of traditional food is threatened to be shifted or replaced by the presence of ready-to-eat food, which is intensively promoted in various media, with the main target being the young age group. This study aimed to determine student’s preferences in Pontianak towards traditional food in West Kalimantan and compare its nutritional composition with ready-to-eat food. This research was conducted using a survey to 150 respondents using online questionnaire. Data were analyzed by the Chi-Square program. The three types of traditional foods that respondents liked the most were tested for their nutritional composition and compared with the nutritional composition of ready-to-eat foods like chicken nugget, hamburger, and fried chicken. The results showed that students in Pontianak had a high preference (90.7%) for traditional West Kalimantan food. West Kalimantan's most preferred traditional foods were kerupuk basah (n=51), bubur pedas (n=49), and ikan asam pedas (n=25). The results showed a relationship between student preferences for food knowledge, nutritional information, taste, and appearance of traditional West Kalimantan foods. The nutritional composition test showed that, in general, traditional foods have higher water content and lower fat content than ready-to-eat food.